2013
DOI: 10.1016/j.ajic.2013.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Student nurses' experiences of infection prevention and control during clinical placements

Abstract: BackgroundLittle is known about nursing students' experiences of infection control in the clinical setting despite its importance protecting patients and reducing risks of occupational exposure. MethodsOnline survey involving a fixed choice Likert-type scale with nineteen items and an open question to solicit more detailed information with a national sample of student nurses in the United Kingdom. ResultsFour hundred and eighty eight student nurses completed questionnaires. All participants reported lack of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 15 publications
0
28
0
7
Order By: Relevance
“…Consistent with published reports, we found that student nurses were knowledgeable and cognizant of infection prevention concepts as evidenced by their ability to identify and provide instances of non-compliance in the hospital. Studies consistently show that student nurses observe discordance in infection prevention expectations and behaviors between the classroom and patient-care setting (Cox et al, 2014; Geller et al, 2010; Gould and Drey, 2013). Geller et al (2010) analyzed 3492 comments related to hazards and near-misses reported by student nurses during clinical rotations and found that nearly one-quarter of comments were infection related.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with published reports, we found that student nurses were knowledgeable and cognizant of infection prevention concepts as evidenced by their ability to identify and provide instances of non-compliance in the hospital. Studies consistently show that student nurses observe discordance in infection prevention expectations and behaviors between the classroom and patient-care setting (Cox et al, 2014; Geller et al, 2010; Gould and Drey, 2013). Geller et al (2010) analyzed 3492 comments related to hazards and near-misses reported by student nurses during clinical rotations and found that nearly one-quarter of comments were infection related.…”
Section: Discussionmentioning
confidence: 99%
“…Poor infection control practices observed by the students can have a negative impact on learning and future practice (Al-Hussami & Darawad, 2013;Gould & Drey, 2013;Hinkin & Cutter, 2014;Ward, 2010).…”
Section: Studentsmentioning
confidence: 99%
“…In this standard, the scientific knowledge conveyed in the basic cycle is not contextualized and appears as a neutral, linear and cumulative conception of knowledge, in comparison to a building, which cannot have a roof without a foundation. (20,21) The use of antimicrobials and its standardization seem to be another challenge which deserve urgent investments to reduce the use of antimicrobials, establish a surveillance system and procedures to prevent contamination and transmission of multidrug-resistant strains in households and communities. (22) Considering the originality that characterizes the actions of home care nurses, particularly due to the absence of an infection control program in this context, the competences listed in this study highlight aspects that should be analyzed also in teaching environments.…”
Section: Contextual Knowledge (Xk) Dimensionmentioning
confidence: 99%